HUBUNGAN DISIPLIN KERJA DAN PENGEMBANGAN SUMBER DAYA MANUSIA DENGAN KINERJA KARYAWAN BPJS KESEHATAN CIKARANG DI KABUPATEN BEKASI: HUBUNGAN DISIPLIN KERJA DAN PENGEMBANGAN SUMBER DAYA MANUSIA DENGAN KINERJA KARYAWAN BPJS KESEHATAN CIKARANG DI KABUPATEN BEKASI - Denny Dwi; Retno Purwani Setyaningrum (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to test 1) Knowing the relationship between work discipline and employee performance at BPJS Kesehatan Cikarang; 2) Knowing the relationship between human resource development and employee performance at BPJS Kesehatan Cikarang; 3) Knowing the relationship between work discipline and human resource development together with employee performance at BPJS Kesehatan Cikarang. The research method used in this study is quantitative method. The population studied was all employees of BPJS Kesehatan Cikarang totaling 102 people. This study used a total sample, where the entire population of BPJS Kesehatan Cikarang employees was used as a sample. The data analysis techniques used are descriptive statistical analysis and inferential analysis (prerequisite analysis test and hypothesis test). Data validity is obtained through validity tests and reliability tests. The results of this stud are as follows: First, there is a positive and significant relationship between work discipline and employee performance with a significance value in a simple correlation of 0.049 (Sig0< 0.05). Second, there is a positive and significant relationship between human resource development and employee performance with a significance value in a simple correlation of 0.000 (Sig < 0.05). Third, there is a positive and significant relationship between work discipline, human resource development, and employee performance with a significance value in a simple correlation of 0.001 (Sig < 0.05).